Mathematical methods for surface and subsurface hydrosystems - Wang, Deguan; Duquennoi, Christian; Ern, Alexandre, 1967- (Series in contemporary applied mathematics, 2006)
With the increasing awareness of the heavy burden placed on environmental resources and the need for industry and public institutions to cope with more stringent regulations, this timely book focuses on some specific, but very important, environmental problems, namely, surface and subsurface hydrosystems. Covering state-of-the-art techniques to model such systems, the volume will be of great benefit to all researchers in applied mathematics and environmental engineering.